Effect of carbon content of ferromanganese alloy on corrosion behaviour of MgO–C refractory. (January 2014) - Um, H.; Lee, K.; Kim, K.-Y.; Shin, G.; Chung, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> The corrosion of MgO–C refractories during decarburisation of liquid ferromanganese alloys was investigated using the finger rotating test. An oxide layer containing MnO is formed on the surface of the MgO–C refractories in contact with molten low carbon ferromanganese alloys (Fe–75Mn–0·8C) but is not formed when the refractories are in contact with high carbon ferromanganese alloys (Fe–75Mn–7C). The thickness of the oxide layer decreases with increasing carbon content in the ferromanganese alloy and increases with immersion time. We conclude that the formation of the oxide layer strongly depends on the driving force, which is the difference in carbon content between MgO–C refractories and molten ferromanganese alloys.